Efektivitas Strangulasi terhadap Pembungaan Tanaman Jeruk Pamelo ‘Cikoneng’ (Citrus grandis (L.) Osbeck) pada Tingkat Beban Buah Sebelumnya yang Berbeda - Thamrin, Muhammad; Susanto, Slamet; Santosa, Edi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2009)
Biannual bearing fruit is a common phenomenon in tropical fruit trees. However, effectiveness of flowering induction on those fruits is still lack of study. The ojective of the research was to study the effectiveness of flowering induction on pummelo of different fruit load on previous year. Field experiment was conducted at farmer's orchad Bantarmara village, Cisarua, Sumedang Region, West Java (300 m above sea level) from August 2007 to April 2008. Experiment was carried out using Completely Randomize Block Design. Experiment was combination of high crop load and less crop load with strangulation position at main stem and primary branches. The results showed that crop load of previous year (higher and less) with strangulation position at primary branches had significant response to the number of  flower clusters, flower buds, bloming flower, fruits formed, and fruit sets as compared to control, when strangulated at primary branches. Nevertheless,  amount of fruit sets, level of greenness leaf and leaf area seened were not determined by fruit load non position of strangulation. This finding implies that fruit load management is an important factor in determining the success of flowering induction using strangulation.   Key words: fruit load, strangulation, pummelo, flowering induction